ASUHAN KEBIDANAN BERKELANJUTAN PADA IBU HAMIL DENGAN TEKNIK GYMBALL UNTUK NYERI PUNGGUNG DAN PEMBERIAN REBUSAN KAYU MANIS UNTUK PENYEMBUHAN LUKA PERINEUM: Continuous Midwifery Care For Pregnant Women Using The Gymball Technique For Back Pain And Administering Decorated Cinnamon For Healing Perineal Wounds - Hatini, Puji; Maharani Besmaya, Beniqna (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2025)
Lower back pain felt by pregnant women as gestational age increases is physiological. The back pain that mothers feel is caused by pressure due to the growth of the uterus which causes changes in the pregnant woman's body posture, resulting in pressure on the curvature of the spine. Using a gymball during pregnancy will stimulate postural reflexes and maintain the muscles that support the spine. This woody tree plant has a very important genus, namely Cinnamomum or cinnamon. Cinnamon contains essential oils (cinnamylaldehyde, eugenol, terpenes), fatty starches, and tannic substances. Likewise with one of the derivatives of the eugenol compound, namely isoeugenol, which can be used as a raw material for antiseptic and analgesic drugs.This case study uses the form of a case study with SOAP method documentation. The subjects of this case study were 3 pregnant women and 3 postpartum mothers in the Gisting work area, Tanggamus Regency providing continuous midwifery care. The aim of this research is to analyze the effect of the gymball technique for treating back pain in pregnant women and administering herbal cinnamon decoction for healing perineal wounds in postpartum women. The results of this research have a quite significant influence.